(untitled) (Світ фінансів, 2017)
Заклекта О. С. Інвестування заходів з розвитку персоналу на українських підприємствах. Здійснено аналіз сучасного стану інвестування заходів з розвитку персоналу в Україні. Розглянуто стратегії організації навчання персоналу, що використовуються на вітчизняних підприємствах та виявлено їх недоліки. Сформульовано пропозиції щодо активізації інвестицій на підготовку, перепідготовку та підвищення кваліфікації працівників. Zaklekta O. The modern condition of measures investing on personnel development at Ukrainian enterprises. The modern condition analysis of measures investing on personnel development in Ukraine is carried out. The strategies of personnel studies organization which are used on domestic enterprises and their disadvantages are considered. The suggestions in reference to multiplying the volumes of investments on preparation, retraining and heightening of employee’s qualification are formulated.